Aspek Yuridis Dan Prosedur Pembebasan Hak Atas Tanah Untuk Pembangunan Kepentingan Umum - Sarkawi - (Jatiswara, 2011)
Execution liberation land right for development base on public interest must be on procedure that commended on law and regulation especially related by liberation to land right for development base on public interest. One of law and regulated are UUPA number 5 year 1960 as the top of regulated about land and as the main gate of human right to land right, beside that many regulation that related to liberation land right for execution development base on public interest. In the contex of requirement of land are relation closely by legality of pallet ownership that oftenly make problem on practice especially in processes for liberation to right land for exeploited development base on public interest, the social right in mastered land and perpetrator development oftenly use development mission for publict interest that forgetting the mean of welfare and social need. Therefore the fact in execution liberation land right must be done by deliberation of general consensul among owner of land with the government, so will be doing by applicant of land liberation, before that the land will be analysis with suitable development creteria by Bappeda and than inviting land owner to look for the suitable price without to prejudicate the right owner of land and than payed according wide of the land.